Week by week plans for documenting children's development - Nilsen, Barbara (Cengage, 2023)
"Week by Week is a documentation system guidebook for students and practitioners in early childhood education who work with infants through second-grade children. Each chapter has two main parts: the documentation method ("Using the Observation Method") and the child development overview ("Looking at Child Development Domain") The purpose is to organize and plan intentionally, week by week, to build a Portfolio for each child, filling it with various pieces of evidence that document the child's development and behavior. Week by Week presents a manageable plan that will help gather documentation on all the children in the class or group, in all the developmental areas"--